Aggregation-Induced Emission Set: Fundamentals and Applications - Qin, Anjun (Editor); Tang, Ben Zhong (Editor) (Wiley [Imprint] Hoboken : John Wiley & Sons, Incorporated, 2013)
Annotation Edited by Professor Tang, who first discovered this phenomenon, this 2-volume reference addresses the fundamentals of Aggregation-Induced Emission (AIE). The book presents an overview of this rapidly emerging and exciting area of research, inviting scientists to renew their photophysical knowledge and stimulate new developments in the field. Covering fundamental issues of AIE, this reference work also discusses the design and synthesis of AIE-active molecules; includes an introduction to AIE, polymers with AIE characteristics and crystallization-induced emission enhancement. Mechanistic understanding of AIE processes are included, along with a discussion of the progress in the theoretical investigation of AIE mechanism and understanding of AIE mechanism by time-resolved spectrum measurements.
Trade
Keywords: Electroluminescent Device; Photoemission; Aggregation; Organosilicon Compounds-Optical Properties; Chemistry